Competencies of Teaching Personnel in the Use of Information Technology (IT) At State Middle School 8 Satu Atap (Satap) Telaga Biru - Sarwin, Sarwin; Tilome, Apris Ara; Pakudu, Robin; Suprapto, Sri Handayani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to determine the level of competency of educators in the use of information technology (IT) at SMP Negeri 8 Satu Atap (SATAP) Telaga Biru Competence in IT mastery is an important indicator in supporting the effectiveness of the learning process in the digital era. This study used a descriptive approach with qualitative methods. Data were collected through interviews, observations, and documentation with teachers and other educational staff at the school. The results indicate that most educators have a basic understanding of information technology use, such as computer operation, office applications, and utilizing the internet as a learning resource. However, there are still limitations in optimally using IT for leaming activities, particularly in integrating technology with teaching methods. Factors influencing IT competency include education level, age, training received, and the availability of technology facilities at the school. Therefore, improving competency through ongoing training and providing supporting resources is essential to foster digital transformation in the educational environment.